Optimalisasi Pendidikan Inklusif: Peran Teknologi Adaptif dalam Meningkatkan Well-Being Anak Berkebutuhan Khusus - Wulandani, Nur (Arus Jurnal Pendidikan, 2025)
Inclusive education in Indonesia continues to face complex challenges such as limited infrastructure, social stigma, and low teacher competencies, which affect the well-being of children with special needs (ABK). This study explores the optimization of inclusive education through the use of adaptive technology based on artificial intelligence (AI) to improve ABK’s school-related subjective well-being. A literature review of 30 scholarly articles (2021–2025) using thematic analysis identified five major themes: (1) structural and psychological barriers in implementing inclusion, (2) the potential of AI as adaptive technology for early detection and personalized learning, (3) the influence of inclusion on ABK well-being shaped by family and social support, (4) the integration of religious-cultural values to strengthen social acceptance, and (5) the importance of educational interventions through teacher training. The findings highlight that inclusive approaches integrating adaptive technology, cultural values, and teacher training can enhance ABK well-being and provide a foundation for responsive educational practices in Indonesia.